A virtual reality based app to educate health care professionals and medical students about inflammatory arthritis: Feasibility study - Klemm, Philipp; Kleyer, Arnd; Tascilar, Koray; Schuster, Louis; Meinderink, Timo; Steiger, Florian; Lange, Uwe; Möller-Ladner, Ulf; Knitza, Johannes; Sewerin, Philipp; Mucke, Johanna; Pfeil, Alexander; et al. (JMIR Serious Games, 2021)
Background: Inflammatory arthritides (IA) such as rheumatoid arthritis or psoriatic arthritis are disorders that can be difficult to comprehend for health professionals and students in terms of the heterogeneity of clinical symptoms and pathologies. New didactic approaches using innovative technologies such as virtual reality (VR) apps could be helpful to demonstrate disease manifestations as well as joint pathologies in a more comprehensive manner. However, the potential of using a VR education concept in IA has not yet been evaluated. Objective: We evaluated the feasibility of a VR app to educate health care professionals and medical students about IA. Methods: We developed a VR app using data from IA patients as well as 2D and 3D-visualized pathological joints from X-ray and computed tomography generated images. This VR app (Rheumality) allows the user to interact with representative arthritic joint and bone pathologies of patients with IA. In a consensus meeting, an online questionnaire was designed to collect basic demographic data (age, sex); profession of the participants; and their feedback on the general impression, knowledge gain, and potential areas of application of the VR app. The VR app was subsequently tested and evaluated by health care professionals (physicians, researchers, and other professionals) and medical students at predefined events (two annual rheumatology conferences and academic teaching seminars at two sites in Germany). To explore associations between categorical variables, the ? 2 or Fisher test was used as appropriate. Two-sided P values =.05 were regarded as significant. Results: A total of 125 individuals participated in this study. Among them, 56% of the participants identified as female, 43% identified as male, and 1% identified as nonbinary; 59% of the participants were 18-30 years of age, 18% were 31-40 years old, 10% were 41-50 years old, 8% were 51-60 years old, and 5% were 61-70 years old. The participants (N=125) rated the VR app as excellent, with a mean rating of 9.0 (SD 1.2) out of 10, and many participants would recommend use of the app, with a mean recommendation score of 3.2 (SD 1.1) out of 4. A large majority (120/125, 96.0%) stated that the presentation of pathological bone formation improves understanding of the disease. We did not find any association between participant characteristics and evaluation of the VR experience or recommendation scores. Conclusions: The data show that IA-Targeting innovative teaching approaches based on VR technology are feasible.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Feasibility; Inflammatory arthritis; Psoriatic arthritis; Rheumatoid arthritis; Virtual reality

Benzonitrile-driven discharge of potassium-intercalated carbon allotropes - Steiger, Florian; Edelthalhammer, Konstantin; Lucherelli, Matteo Andrea; Wabra, Isabell; Requena-Ramírez, Julia; Castro, Edison; Hauke, Frank; Echegoyen, Luis; Hirsch, Andreas; Abellán, Gonzalo; Perez-Ojeda Rodriguez, Maria Eugenia (Carbon, 2025)
In this work we performed a comprehensive investigation, exploring the reduction of synthetic carbon allotropes (SCAs) via alkali metal intercalation. Carbon nanotubes (CNTs), carbon nano-onions (CNOs), and fullerenes (C60&C70) were employed, focusing on post-intercalation electron transfer efficiency and mass transport dynamics with benzonitrile (PhCN). Our study revealed the feasibility of discharging residual negative charges in all allotropes, exhibiting different electron transfer ratios (ETR) dependent on morphological factors. Notably, CNT length played a crucial role, shorter HiPco nanotubes displayed a significantly higher ETR (55 %) compared to longer arc discharge nanotubes (15 %), highlighting the influence of nanotube length on intercalation kinetics. Further investigation into CNOs unveiled a relatively high ETR of 80 % for untreated CNOs and a low ratio of 24 % for oxidized onions, underlining the critical role of size distribution and surface chemistry. Inner shell entrapment of potassium reduces accessibility in CNOs, as confirmed by TGA-MS and XPS experiments. Our analysis underscored the impact of disparate electron affinities and molecular structures on electron transfer dynamics, as seen in our fulleride analysis, where reversible electron uptake from fullerides to solvent occurred, more pronounced for C60 than C70. Overall, our findings demonstrated that CNTs and CNOs share similar mechanisms with graphenides, however, mass transport is limited by potassium accessibility. In contrast, molecular fullerenes exhibit distinct behavior due to competitive redox processes. Additionally, our investigation highlighted the utility of PhCN treatment in facilitating the recovery of pristine materials and mitigating undesired side functionalization post-exposure to moisture, thereby enabling the protocol's generalization across various SCA
Keywords: SCAs; CNT; Fullerenes; Carbon nano-onions; Reductive functionalization; Electron trapping mass transport; PhCN•- radical anion

Carbon nano-onions: Individualization and enhanced water dispersibility - Lucherelli, Matteo Andrea; Stiegler, Lisa; Steiger, Florian; Åhlgren, E. Harriet; Requena-Ramírez, Julia; Castro, Edison; Echegoyen, Luis; Hirsch, Andreas; Peukert, Wolfgang; Kotakoski, Jani; Walter, Johannes; Perez-Ojeda Rodriguez, Maria Eugenia; et al. (Carbon, 2024)
Carbon nano-onions (CNOs) are a unique class of carbon nanomaterials, with a concentric fullerene-like structure and sp2-hybridized carbon atoms. Onions present high mechanical strength, good conductivity, the capability to intercalate alkali metals, showing promising applications in diverse fields, such as tribology, energy storage, and nanomedicine. Their production has been developed by several techniques, with the most interesting being the thermal annealing of carbon nanodiamonds because of the easy scalability (gram-scale) and morphologic control (size and shape form perfectly spherical to polygonal). However, this synthesis is commonly affected by the formation of strong aggregates larger than 100 nm, attributed to carbon soot formation or strong van der Waals interactions, hindering the work with small and individual particles, leading to an altered yield of functionalization. In this study we propose a method for CNO individualization based on strong acid treatment, yielding highly water dispersible nanoparticles. Analytical ultracentrifugation (AUC) analysis is employed as a technique to investigate the particle dimensions directly in dispersion, permitting an ensemble analysis free from further sample preparation bias. Moreover, we also provide a comprehensive evaluation of the common post-synthetic treatment methods, and their effects. By means of scanning transmission electron microscopy with medium angle annular dark field detector and electron energy loss spectroscopy (STEM-MAADF and EELS) we have shown images of individual CNOs. Their successful separation achieved in this study is significant for future research and applications in nanomedicine, electrochemistry, and materials composites, where sample homogeneity is critical.<br
CRIS-Team Scopus Importer:2024-01-12
Keywords: Analytical ultracentrifugation; Carbon materials; Carbon nano-onions; Exfoliation; Materials chemistry

Improving Oxygen Reduction Reaction ORR Fuel Cell Efficiency with Carbon Nano Onions - Steiger, Florian; Kaiser, Pascal; Assebban, M'hamed; Hirsch, Andreas; Abellan, Gonzalo; Echegoyen, Luis; Mayrhofer, Karl J. J.; Cherevko, Serhiy; Perez-Ojeda Rodriguez, Maria Eugenia; Lloret Segura, Vicente Josep (243rd ECS Meeting with the Eighteenth International Symposium on Solid Oxide Fuel Cells, 2023)
Hydrogen Fuel cell innovations are cutting-edge clean power solutions highly demanded nowadays. Since the oxygen reduction reaction (ORR) in fuel cells needs to be catalyzed heterogeneously, conductive substrates such as carbon materials are critical for the construction of electrocatalysts. Thus far, the research has been focused on commercially available carbon supports such as the well-known Vulcan, and the high-surface area Ketjenblack.[1] Thanks to the fast development of material science, other carbon supports such as graphite, graphene oxide, and carbon nanotubes have been also studied in a lesser extent, mainly due to their novelty and underdeveloped scale up syntheses.[2,3] This work focuses on utilizing a relatively new and, as of yet, largely unexplored carbon nanomaterial: carbon nano onions (CNOs). CNOs are spherical nanoparticles of about 5 nm diameter composed of concentrical multi-layered fullerenes, first discovered by Ugarte in 1992. CNOs exhibit outstanding properties such as low density, high thermal stability, and a graphitic multilayer morphology, which makes them excellent candidates for a wide variety of applications. Furthermore, the onion's large surface area and high conductivity make them particularly interesting as catalyst support for electrochemical applications as they have already been demonstrated to be a superior Pt support alternative thanks to a higher cycling stability compared to carbon black, since their particle size and morphology suppress catalyst agglomeration and avoid its ripening.[4] However, despite their excellent long-term stability, the few available studies using CNOs were performed using the rotatory disc electrode (RDE) method, reaching only modest performance in the mA / cm2 range. Thus, our work aims to further extend upon this research by measuring the ORR performance with a gas diffusion electrode (GDE), to reproduce realistic fuel cell conditions.[5] The catalyst layer, obtained by growing Pt nanoparticles on CNOs, is characterized by electrochemical measurements such as ORR polarization curves, electrochemical active surface area (ECSA) by the CO-stripping method, and O2-mass transport. The utilization of GDE cells allows for higher current densities and a realistic catalyst mass transport compared to the RDE method, thus better representing an applied ORR fuel cell test.[